Effectiveness Of The Educational Intervention Program On The Level Of Knowledge About Anemia Among Teenage Females - Heni Marliany; Ima Sukmawati; Aap Apipudin; Devia Deliani (Program Studi Keperawatan Universitas Muhammadiyah Tasikmalaya, 2023)
Anemia is a medical condition in which the number of red blood cells or hemoglobin is less than 12 grams/100 ml. One of the efforts to increase one's knowledge about anemia is through health education which is one of the efforts to prevent anemia in adolescent girls. The aim is to determine the effect of health education about anemia on the level of knowledge of adolescent girls at SMA Negeri 1 Cisaga. This study used the Pre-Experimental method, the design used was One Group Pre-Test and Post-Test. Sampling using Non Random Sampling as many as 69 respondents. The results show that Knowledge of adolescent girls before the pre-test was on average 46.91. While after the posttest it increased to 78.61. Based on the Paired Sample T-test test, it shows that Ha is accepted with a Sig (2-tailed) value = 0.000 <0.05. In conclusion, there is an influence between the level of knowledge of adolescent girls at SMA Negeri 1 Cisaga with health about anemia.